The new political targeting - Malchow, Hal. (Washington, DC : Campaigns and Elections Magazine, 2003)
Accompanying CD-ROM contains ... "segmentation tables." -- CD-ROM label.
Includes bibliographical references and index.
System requirements: Windows 95 or newer, Microsoft Office Suite 1998 or newer with Microsoft Excel installed.
Keywords: Voting research -- United States; Politics, Practical -- United States; Elections -- United States